Dysbiosis of Gastric Mucosal Fungal Microbiota in the Gastric Cancer Microenvironment - Zhenzhan Zhang; Hao Feng; Yaopeng Qiu; Zhou Xu; Qingfeng Xie; Wenfu Ding; Hao Liu; Guoxin Li (Journal of Immunology Research)
Background. Microbes have been shown to contribute to gastric cancer (GC), gastric bacteria and viruses are associated with gastric carcinogenesis. However, the relationship between gastric fungi and GC is still unclear. Our aim was to evaluate the gastric fungal microbiota in the GC microenvironment. Methods. Gastric fungal microbiome profiling was performed with internal transcribed spacer (ITS) rDNA sequencing in primary tumor and corresponding paired normal mucosal tissues from 61 GC patients. Differences in microbial composition, taxa diversity, and predicted function were further analyzed. Results. Dysbiosis of gastric mucosal fungal microbiome was observed between the tumor and normal groups in GC. The tumor group had a higher abundance of certain taxa than the normal group. In the taxa classification, the abundances of Pezizomycetes, Sordariales, Chaetomiaceae, and Rozellomycota were lower in the tumor group than in the normal group. At the genus level, Solicoccozyma (P=0.033) was found in higher abundance and was differentially enriched in the tumor group with Lefse analysis. Additionally, Solicoccozyma accounted for 0.3% of gastric fungi in the GC microenvironment. Twenty-seven of the 61 GC patients showed positive Solicoccozyma expression in tumors. Solicoccozyma-positive expression in tumors was associated with the Bormann classification and nerve invasion. Solicoccozyma was considered a gastric fungal marker to classify stage I and stage II-IV GC patients with an area under the receiver-operating curve (AUC) of 0.7061, as well as to classify the nerve invasive and nonnerve invasive tumors from GC patients with an AUC of 0.6978. Functional prediction indicated that the positive expression of Solicoccozyma in tumors was associated with the amino acid- and carbohydrate-related metabolic pathways in GC. Conclusions. This study revealed a novel perspective on the role of Solicoccozyma in tumors and a theoretical basis for therapeutic targets against GC.